Effects of green manure planting mode on the quality of Korla fragrant pears (Pyrus sinkiangensis Yu) - Han, Sujian; Zhao, Jinfei; Liu, Yang; Xi, Linqiao; Liao, Jiean; Liu, Xinying; Su, Guangdong (Frontiers in Plant Science, 2022)
A three-year experiment on the fragrant pear orchard was conducted to investigate the effects of different types of green manure on the fruit quality traits of Korla fragrant pear, in order to find a suitable green manure planting pattern for Korla fragrant pear orchard. In their full bloom period, green manures were planted in spaces between rows of pear trees and then smashed and pressed into the soil by agricultural machinery equipment as fertilisers. In the experiment, four planting modes of green manure were set for comparison: SA: leguminous green manure alfalfa (Medicago sativa L.); SP: poaceae green manures oats (Avena sativa L.); ST: cruciferae green manures oilseed rape (Brassica napus L.); and S: orchard authigenic green manures (antigenic grass). Eleven fruit quality indicators were chosen for analyzing to evaluating the effects of different green manure planting patterns on the quality of fragrant pear. Based on the principal component analysis (PCA) results, a comprehensive evaluation model of fruit quality was built. Moreover, the influences of green manure planting modes on the fruit quality of Korla fragrant pears were discussed by comparing fruit quality traits. According to Analysis of variance (ANOVA) results, there were significant differences among four planting modes in terms of eight fruit quality indicators (P<0.05), while the coefficient of variation (CV) of 11 indicators ranged from 2.50% to 17.09%. According to the correlation analysis (CA) results, there were different degrees of correlations among quality indicators. On this basis, repeated information among indicators was eliminated by PCA, thus simplifying and recombining the three principal components. These three principal components reflect appearance traits, internal nutritive value and taste of fruits, respectively. Specifically, SA significantly improves the internal quality and nutritive value of fruits. SP improved the physical traits of fruits. ST significantly improved the taste of fruits. There are comprehensive fruit quality scores: SA>SP>ST>S.